Pembangunan Aplikasi Entertainment Terminal Berbasis Sistem Kendali Head Movement Control System pada Perangkat IOS - Muhammad Reyhan; Herman Tolle; Lutfi Fanani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Along with technological developments, smartphones have become a very commonly used device. Smartphones have also been equipped with sensors that can increase the functionality of the device. With the existence of human smartphones as users have gained a lot of conveniences that are not only limited to communication, but also in accessing entertainment. Through smartphone users can access digital entertainment content such as music and movies. But not everyone can enjoy this entertainment, especially users with physical limitations on the hands. With the movement sensor on the smartphone has been developed HEMOCS method to read the head movement that can be used for navigation in applications and with this method can be made an application Entertainment Terminal to meet the needs of entertainment for users. The app provides digital content like music, movies, and tv. With this application, users with physical limitations can access the entertainment. In the implementation of the Entertainment Terminal, application uses HEMOCS as control to obtain valid functionality results with an accuracy of 86%.